Carney complex and other conditions associated with micronodular adrenal hyperplasias - Almeida, Madson Q. (2010)
Carney complex (CNC) is a multiple neoplasia syndrome that is inherited in an autosomal dominant manner and is characterized by skin tumors and pigmented lesions, myxomas, schwannomas, and various endocrine tumors. Inactivating mutations of the PRKAR1A gene coding for the regulatory type I-α (RIα) subunit of protein kinase A (PKA) are responsible for the disease in most CNC patients. The overall penetrance of CNC among PRKAR1A mutation carriers is near 98%. Most PRKAR1A mutations result in premature stop codon generation and lead to nonsense-mediated mRNA decay. CNC is genetically and clinically heterogeneous, with specific mutations providing some genotype-phenotype correlation. Phosphodiesterase-11A (the PDE11A gene) and −8B (the PDE8B gene) mutations were found in patients with isolated adrenal hyperplasia and Cushing syndrome, as well in patients with PPNAD. Recent evidences demonstrated that dysregulation of cAMP/PKA pathway can modulate other signaling pathways and contributes to adrenocortical tumorigenesis.